Relationship Between Mother's Behavior and Child's Readiness in the Weaning Process - Alifa Sandri Yeni; Erika Erika; Nurul Huda (CV. Rayyan Dwi Bharata, 2023)
Weaning from breast milk (ASI) is a process of stopping breastfeeding gradually. Positive mother's behavior will form a good child's readiness for the successful weaning process of breastfeeding. This study used a correlative descriptive research design with a cross sectional approach. Respondents in this study were 87 mothers who carried out weaning from breastfeeding in the working area of the Rejosari Health Center. The research samples were taken based on inclusion criteria using a purposive sampling technique. The analysis used univariate analysis to see the frequency distribution and bivariate analysis using the Chi-Square test. The statistical test results showed that there was a relationship between mother's behavior and child's readiness in the weaning process with p-value (0.002) alpha (0.05). The results of this study indicate that the mother's behavior is related to the readiness of the child in the weaning process.